"Yields and nutrient pools in soils cultivated with Tectona grandis and Gmelina arborea in Nigerian rainforest ecosystem" (2011)
This study examined the yield of the two most prominent exotic species in southwest Nigeria and the nutrient status of soils cultivated with these species. The impacts of plantation development on soil nutrients were also examined. The plantations species are Gmelina arborea (Gmelina) stands established in 1984, 1988, 1990 and 1994 and Tectona grandis (Teak) established in 1990, 1992, 1994, 1996 and 1997. Growth data and composite soil samples from 3 depths (0–15, 15–30 and 30–60 cm) were collected from five equal sized plots (20 • 20 m2) randomly located in the plantation of the two species. Also, soil samples were collected from the adjacent natural forest for comparison. The results for both species show that tree growth variables increased substantially with increase in tree age. There was significant difference in number of trees per hectare, dominant diameter, volume/ha and MAI for the Gmelina stands. In the Teak stand, there was significant difference in most of the tree growth variables also. Nutrients required by plants to survive were present in the soil samples from the plantations and the natural forest in different proportions. There was high correlation between percentage sand and most of the tree growth variables for both species. The pH value obtained for the Gmelina stands ranged between 6.47 and 7.47 while that of Teak stands ranged between 5.57 and 8.33. There was also a high and positive relationship between